Use of remdesivir in patients with COVID-19: a systematic review and meta-analysis - Tanni, Suzana E. [UNESP]; Silvinato, Antonio; Floriano, Idevaldo; Bacha, Hélio A; Barbosa, Alexandre Naime [UNESP]; Bernardo, Wanderley M. (Sociedade Brasileira de Pneumologia e Tisiologia, 2022)
OBJECTIVE: Studies in the literature regarding the use of remdesivir to treat COVID-19 patients have shown conflicting results. This study sought to answer questions related to the use of remdesivir for the treatment of patients hospitalized with moderate to severe COVID-19. METHODS: This was a systematic review and meta-analysis including phase 3 randomized clinical trials (RCTs) and observational cohort studies selected from various databases, comparing patients hospitalized with moderate to severe COVID-19 receiving remdesivir and controls. RESULTS: A total of 207 studies were retrieved, 9 of which met the eligibility criteria and were included in the study. The meta-analysis using RCTs alone showed no statistically significant differences regarding mortality or use of mechanical ventilation/extracorporeal membrane oxygenation between remdesivir and control groups, and the quality of evidence was moderate and low, respectively. The use of remdesivir increased the recovery rate by 6% (95% CI, 3-9); p = 0.004) and the clinical improvement rate by 7% (95% CI, 1-14); p = 0.02). Additionally, no significant differences in mortality were found between remdesivir and control groups when the meta-analysis used observational cohort studies alone (risk difference = -0.01 (95% CI, -0.02 to 0.01; p = 0.32), the quality of evidence being moderate, and the risk of adverse events was 4% ([95% CI, -0.08 to 0.01]; p = 0.09). CONCLUSIONS: The use of remdesivir for the treatment of patients with moderate to severe COVID-19 had no significant impact on clinically important outcomes.